Work and the workplace : a resource for innovative policy and practice - Akabas, Sheila H., 1931- (Foundations of social work knowledge., 2005)
For more than twenty years Sheila H. Akabas and Paul A. Kurzman have written extensively about workers and work organizations, and given leadership to the occupational social welfare movement worldwide. Recognized as leaders in their field, Akabas and Kurzman offer an invaluable and comprehensive look at the innovative ways in which management, labor organizations, government, and social workers can better respond to the needs of workers, their families, and communities. The authors consider the social, psychological, and economic conditions in the world of work; the domino im.